A plethora of diffuse steep spectrum radio sources in Abell 2034 revealed by LOFAR - Shimwell, T.; Luckin, J.; Brüggen, M.; Brunetti, G.; Intema, Hubertus; Owers, M.; Röttgering, H.; Stroe, A.; Van Weeren, R.; Williams, W.; Cassano, R.; De Gasperin, F.; et al. (Oxford University Press, 2016)
With Low-Frequency Array (LOFAR) observations, we have discovered a diverse assembly of steep spectrum emission that is apparently associated with the intracluster medium (ICM) of the merging galaxy cluster Abell 2034. Such a rich variety of complex emission associated with the ICM has been observed in few other clusters. This not only indicates that Abell 2034 is a more interesting and complex system than previously thought but it also demonstrates the importance of sensitive and high-resolution, low-frequency observations. These observations can reveal emission from relativistic particles which have been accelerated to sufficient energy to produce observable emission or have had their high energy maintained by mechanisms in the ICM. The most prominent feature in our maps is a bright bulb of emission connected to two steep spectrum filamentary structures, the longest of which extends perpendicular to the merger axis for 0.5 Mpc across the south of the cluster. The origin of these objects is unclear, with no shock detected in the X-ray images and no obvious connection with cluster galaxies or AGNs. We also find that the X-ray bright region of the cluster coincides with a giant radio halo with an irregular morphology and a very steep spectrum. In addition, the cluster hosts up to three possible radio relics, which are misaligned with the cluster X-ray emission. Finally, we have identified multiple regions of emission with a very steep spectral index that seem to be associated with either tailed radio galaxies or a shock.